2007
DOI: 10.1212/01.wnl.0000271382.62776.b7
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent meningioma

Abstract: In this small trial of patients with recurrent meningiomas shown to overexpress somatostatin receptors by octreotide scintigraphy, long-acting somatostatin (Sandostatin LAR) was administered on a monthly schedule. Thirty-one percent of patients demonstrated a partial radiographic response and 44% achieved progression-free survival at 6 months. Toxicity was minimal, suggesting somatostatin analogues may offer a novel, relatively nontoxic alternative treatment for recurrent meningiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
140
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(154 citation statements)
references
References 13 publications
5
140
1
8
Order By: Relevance
“…5,13 A pilot study of sustained-release somatostatin (octreotide acetate) for the treatment of patients with refractory meningiomas (of all World Health Organization [WHO] grades) indentified 3 of 16 (18.8%) patients with octreotidepositive pulmonary lesions. 14 In the current study, 6 cases of metastatic meningioma are presented in which pulmonary meningioma metastases were detected after 111 In-octreotide scintigraphy and in 1 of the cases, meningioma histology was confirmed by surgical resection and pathology analysis.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…5,13 A pilot study of sustained-release somatostatin (octreotide acetate) for the treatment of patients with refractory meningiomas (of all World Health Organization [WHO] grades) indentified 3 of 16 (18.8%) patients with octreotidepositive pulmonary lesions. 14 In the current study, 6 cases of metastatic meningioma are presented in which pulmonary meningioma metastases were detected after 111 In-octreotide scintigraphy and in 1 of the cases, meningioma histology was confirmed by surgical resection and pathology analysis.…”
mentioning
confidence: 80%
“…2,14,22 However, in patients with histologically atypical (WHO grade II) or anaplastic (WHO grade III) tumors, these treatment approaches are almost never curative, with 10-year disease-free survival rates of 13% and 0%, respectively. 14,22 In these patients, treatment with doxorubicin, hydroxyurea, temozolomide, irinotecan, interferon-a, tamoxifen, imatinib, mifepristone, or octreotide acetate have been attempted. 14,22 One study reported that octreotide acetate was found to increase the progression-free survival rate at 6 months to 44% in patients with recurrent meningiomas that expressed somatostatin receptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations